CONTEXTUALIZATION OF QUR’ANIC TEACHINGS IN ISLAMIC ACCOUNTING THROUGH PHILOSOPHY - Budiwibowo, Triyono; Listyorini, and Inon (J-ISCAN: Journal of Islamic Accounting Research, 2025)
This article presents philosophical findings that are consistent with Qur’anic teachings within Islamic Accounting, particularly in the contexts of divinity, humanity, and nature. The purpose of this paper is to trace, through rational analysis, the contextualization of Qur’anic teachings in Islamic Accounting using philosophy, by examining the similarities and differences between the two. This article is a literature review conducted through analytical methods, including analysis, synthesis, interpretation, comparison, and deductive–inductive reasoning. The results of this literature review indicate that philosophy in Islamic Accounting, as a product of human thought, finds its contextualization in the concept of ijtihad in Islam. Philosophical belief is indeed necessary; however, religion represents a totality of belief and practice manifested in the relationship between humans and God, fellow human beings, and the universe